Usage of Dynamic Analysis to Determine Force Interactions Between Components of Rolling Bearings - Kohar, Robert; Hrcek, Slavomir; Medvecky, Stefan (Communications - Scientific letters of the University of Zilina, 2012)
The aim of this paper is to detail the creation of a roller bearing model in the Adams program suite for subsequent dynamic analysis and to obtain information about different parts of the bearing during the simulation. The bearing model was made so as to closely resemble its reallife counterpart, which allows us to estimate load conditions, dynamic conditions of individual bearing parts and interactions between them